SUSCEPTIBILITY STATUS OF PHLEBOTOMUS PAPATASI TO DDT IN THE MOST IMPORTANT FOCUS OF ZOONOTIC CUTANEOUS LEISHMANIASIS, ISFAHAN PROVINCE, IRAN - M.R.Yaghoobi-Ershadi; E. Javadian (Tehran University of Medical Sciences, 1995)
With regard to the importance of determining the susceptibility level of sandflies to insecticides in control operations especially in leishmaniasis foci, the susceptibility status of P.papatasi collected from indoors in several villages in the rural districts of Varzaneh and Borkhar, Isgahan was tested against 4.0% DDT following a standard WHO technique during 1991-92. These species is the main vector of zoonotic cutaneous leishmaniasis and sandfly fever to man. In this program 72 series of susceptibility tests were carried out on a total of 2360 fed P.papatasi collected by aspiration from 6 villages in two rural districts. Our studies showed that P.papatasi is tolerant to DDT in the rural district of Borkhar, north of Isfahan. LT50 and LT90 values were calculated in both areas. Comparisons of LT90 of the two population of P.papatasi in Varzaneh and Borkhar rural districts showed significant differences between them.